Farmers' Knowledge Is the Basis for Local Level Agro-Forestry Management: The Case of Lemo Woreda in Hadiya Zone, Ethiopia - Horamo, Yohannes; Chitakira, Munyaradzi; Yessoufou, Kowiyou (Frontiers in Sustainable Food Systems, 2021)
This research was designed to investigate the hypothesis that farmers practising traditional agro-forestry which dates back for centuries have accumulated immense knowledge of agro-forestry, which can be captured and incorporated into formal development programmes to improve it. Farmers' knowledge must be documented, valued and integrated in order to maximise its importance for planning and decision-making. This research aimed to investigate and document farmers' knowledge of managing agro-forestry and the contribution to sustainable management of natural resources. Accordingly, questionnaire surveys were conducted in six villages from three peasant associations. In total, 73 households were selected for interview and the data collected were analysed using SPSS (Statistical Package for Social Science) version 26. The findings revealed tree species that contribute to crop yield improvement and the important role agro-forestry trees play with regard to soil fertility. Farmers' strategies to associate trees and shrubs in their farmlands were revealed. Tree species with a negative effect on crop yields were identified and recorded. Farmers reported and ranked in the order of importance, opportunities and constraints in the management of agro-forestry. Farmers' accumulated knowledge of tree–crop and tree–animal interactions, the role of trees in soil fertility, crop and livestock improvement, revealed in the study can significantly enhance the stainability of agriculture. If local knowledge is not documented, it remains largely inaccessible to development workers seeking solutions to locally defined problems.